Word and taboo: a reading method and writing in the treatment of the soscial inclusión with young - Robles Mendoza, Román (2009)
A reading and writing inclusive experience developed for a group of students from the Faculty of Social Sciences in a time that the university was controlled by army troops become a youth social inclusion method based in the progressive exploration and domain of the word in the reading of poetry and poetic writing. The design method considers three stages according to the historical role of poetry: first the domain of words, followed by words orders construction and culminates with the meaning constructions. The method considers that reading encourages cognitive function, and writing the manipulative function. And both have a complementary relationship.